Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1080/22221751.2023.2192816
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of an ancient and pathogenic mammarenavirus

Abstract: Emerging zoonoses of wildlife origin caused by previously unknown agents are one of the most important challenges for human health. The Qinghai-Tibet Plateau represents a unique ecological niche with diverse wildlife that harbours several human pathogens and numerous previously uncharacterized pathogens. In this study, we identified and characterized a novel arenavirus (namely, plateau pika virus, PPV) from plateau pikas ( Ochotona curzoniae ) on the Qinghai-Tibet Plateau by virome analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…TCRV) have also been found in Artibeus neotropical leaf-nosed, fruit-eating bats of the Phyllostomidae family [ 10 ]. The plateau pika viruses (PPVs) were found in small, mountain-dwelling mammals called pikas in Asia and Southeast Asia [ 11 , 12 ]. Other mammals, such as the Northern white-breasted hedgehogs in Hungary (Europe), serve as natural hosts for the Mecsek Mountains virus MEMV [ 13 ].…”
mentioning
confidence: 99%
“…TCRV) have also been found in Artibeus neotropical leaf-nosed, fruit-eating bats of the Phyllostomidae family [ 10 ]. The plateau pika viruses (PPVs) were found in small, mountain-dwelling mammals called pikas in Asia and Southeast Asia [ 11 , 12 ]. Other mammals, such as the Northern white-breasted hedgehogs in Hungary (Europe), serve as natural hosts for the Mecsek Mountains virus MEMV [ 13 ].…”
mentioning
confidence: 99%
“…Case in point, a novel arenavirus, named the Plateau Pika virus (PPV), which is capable of infecting mammalian cells, was recently obtained from the plateau pikas (Ochotona curzoniae) on the Qinghai-Tibet Plateau. Phylogenetic analyses revealed that PPV is a very ancient mammarenavirus that diverged from today's lines of New and Old World mammarenaviruses about 77-88 million years ago [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…They are most commonly transmitted by unintentional human contacts with infected virus-ladened rodent urine, droppings, or nesting materials [ 1 ]. Mammarenaviruses are generally divided into two groups, New World and Old World, based on their phylogenetic, serological, and geographical differences [ 4 ]. New World (NW) mammarenaviruses, including several known human pathogens, such as Junin, Machupo, Sabia, Chapare, and Guanarito viruses, are found in North and South America in rodent subfamilies Sigmodontiae and Muridae .…”
mentioning
confidence: 99%
“…More recently, another novel mammarenavirus, called Plateau Pika Virus (PPV), has been isolated from plateau pikas, which are small mammals of the Lagomorpha family, in the Qinghai Tibet Plateau region [ 3 ]. Based on phylogenetic analyses of the genetic sequences of the viral matrix Z protein, the RNA-dependent RNA polymerase (RdRp) L protein, glycoprotein (GP), and nucleoprotein (NP), it is likely that PPV diverged between 77 and 88 million years ago, which would place this newly identified mammarenavirus in a separate lineage that appeared long before the divergence of OW and NW mammarenaviruses ( Figure 1 ) [ 4 ]. RNA sequencing of plateau pika intestinal contents revealed PPV RNA in 34 of 541 (6.3%) of the samples analysed.…”
mentioning
confidence: 99%
See 1 more Smart Citation